2009
DOI: 10.3233/thc-2009-0540
|View full text |Cite
|
Sign up to set email alerts
|

Direct cellular vs. indirect pager communication during orthopaedic surgical procedures: A prospective study

Abstract: Background: Cellular phone use within the hospital setting has increased as physicians, nurses, and ancillary staff incorporate wireless technologies in improving efficiencies, cost, and maintaining patient safety and high quality healthcare [11]. Through the use of wireless, cellular communication, an overall improvement in communication accuracy and efficiency between intraoperative orthopaedic surgeons and floor nurses may be achieved.Methods: Both communication types occurred while the surgeon was scrubbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…For interventions using mobile technologies to communicate between health care providers for clinical/patient management, three trials [40],[43],[46] relied on the use of MMS for sending images by mobile phone, and one trial used the telephone function of the mobile phone [44]. One trial used MMS on a PDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For interventions using mobile technologies to communicate between health care providers for clinical/patient management, three trials [40],[43],[46] relied on the use of MMS for sending images by mobile phone, and one trial used the telephone function of the mobile phone [44]. One trial used MMS on a PDA.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials [26],[34],[36],[38],[39] reported 17 medical process outcomes: perceived difficulty in performing a task (1 outcome) [39], use of tool (1) [36], errors in report (2), errors in score calculation (2) [34], completeness of reports (2) [38], time to complete a report (2) [38], time to record vital signs (1) [34], time to diagnosis (3) [26], and time to treatment (3) [26]. For interventions using mobile technologies to communicate between health care providers for clinical/patient management outcomes, six trials [40],[42]–[44],[46],[57] reported 19 outcomes relating to the quality of nurse surgeon communication (6 outcomes) [44], correct clinical assessment or diagnosis (4) [40],[43],[46], test score (1) [42] and electrocardiogram (ECG) transmission (8) [57], feasibility of delivery (1), time taken (4), and quality (3) [57]). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have focused on calls between hospital coworkers, investigating for instance the telephone communication of physicians (Aziz et al, 2005;Ortega, Taksali, Smart, & Baumgaertner, 2009;Soto, Chu, Goldman, Rampil, & Ruskin, 2006), among the staff of general internal medicine units (Lo, Wu, Morra, Lee, & Reeves, 2012;Whitlow, Drake, Tullmann, Hoke, & Barth, 2014;Wu et al, 2010), between floor nurses and on-call physicians (Bernstam et al, 2007) and between nurses in medical emergency centres and physicians on duty (Tjora, 2000). The majority of the existing studies revolve around safety issues related to mobile phones (Myerson & Mitchell, 2003) and their pros and cons compared with pager-mediated contact Ortega et al, 2009;Soto et al, 2006) and landline telephone use (Hanada, Fujiki, Nakakuni, & Sullivan, 2006). They also examine the usefulness of telephone communication between physicians in terms of continuity of care (Blankenship, Menapace, Fox, & Frey, 1999;Crone, 1987), ways remote and technology-mediated work communication may balance the nurse-physician professional relationship (Tjora, 2000) and the reasons for after-hours nurse-to-physician calls (Bernstam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In many of the existing studies that have explored mobile clinical communication technologies, the methodological design was reported to be of lower quality and based on users’ perceptions [13]. Additionally, only a few randomized controlled experiments were identified [13,16]. …”
Section: Introductionmentioning
confidence: 99%